Astrocyte uncoupling as a cause of human temporal lobe epilepsy. (11th March 2015) - Bedner, Peter; Dupper, Alexander; Hüttmann, Kerstin; Müller, Julia; Herde, Michel K.; Dublin, Pavel; Deshpande, Tushar; Schramm, Johannes; Häussler, Ute; Haas, Carola A.; Henneberger, Christian; Theis, Martin; et al.
Abstract : Increasing evidence suggests glial cell involvement in CNS disorders. Using techniques including patch clamp recording, EEG/video monitoring and fate mapping in human hippocampal tissue and in a mouse model, Bedner et al. reveal a causal role for astrocyte dysfunction in the aetiology of mesial temporal lobe epilepsy with sclerosis. Abstract : Abstract : Glial cells are now recognized as active communication partners in the central nervous system, and this new perspective has rekindled the question of their role in pathology. In the present study we analysed functional properties of astrocytes in hippocampal specimens from patients with mesial temporal lobe epilepsy without ( n = 44) and with sclerosis ( n = 75) combining patch clamp recording, K + concentration analysis, electroencephalography/video-monitoring, and fate mapping analysis. We found that the hippocampus of patients with mesial temporal lobe epilepsy with sclerosis is completely devoid of bona fide astrocytes and gap junction coupling, whereas coupled astrocytes were abundantly present in non-sclerotic specimens. To decide whether these glial changes represent cause or effect of mesial temporal lobe epilepsy with sclerosis, we developed a mouse model that reproduced key features of human mesial temporal lobe epilepsy with sclerosis. In this model, uncoupling impaired K + buffering and temporally preceded apoptotic neuronal death and the generation of spontaneous seizures. Uncoupling was induced through intraperitoneal injection of lipopolysaccharide, prevented in Toll-like receptor4 knockout mice and reproduced in situ through acute cytokine or lipopolysaccharide incubation. Fate mapping confirmed that in the course of mesial temporal lobe epilepsy with sclerosis, astrocytes acquire an atypical functional phenotype and lose coupling. These data suggest that astrocyte dysfunction might be a prime cause of mesial temporal lobe epilepsy with sclerosis and identify novel targets for anti-epileptogenic therapeutic intervention.